The Efficacy of Principle-Based Correctional Counseling for Improving the Self-Control and Mental Health of People Incarcerated for Sexual Violence - Kelley, Thomas M. (Violence against women, 2022)
This study is the first to test the efficacy of principle-based correctional counseling (PBCC) for improving the self-control and mental health of people incarcerated for sexual violence (SV). A total of 132 males incarcerated for SV were assigned to a treatment group that received cognitive behavior therapy (CBT) supplemented with intensive PBCC and a waitlist control group that received only CBT. Results using paired t-tests and an analysis of covariance (ANCOVA) to control for pretest scores showed that compared with the control group, treatment participants showed a significant increase in affective well-being and a significant decrease in low self-control, depression, anxiety, and anger.